STAT-ART: The Promise and Practice of a Rapid Palliative Single Session of MR-Guided Online Adaptive Radiotherapy (ART) - Mittauer, Kathryn E.; Hill, Patrick M.; Geurts, Mark W.; De Costa, Anna-Maria; Kimple, Randall J.; Bassetti, Michael F.; Bayouth, John E. (Frontiers in Oncology, 2019)
This work describes a novel application of MR-guided online adaptive radiotherapy (MRgoART) in the management of patients whom urgent palliative care is indicated using statum-adaptive radiotherapy (STAT-ART). The implementation of STAT-ART, as performed at our institution, is presented including a discussion of the advantages and limitations compared to the standard of care for palliative radiotherapy on conventional c-arm linacs. MR-based treatment planning techniques of STAT-ART for density overrides and deformable image registration (DIR) of diagnostic CT to the treatment MR are also addressed.